2009
DOI: 10.1007/s10439-009-9709-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Flow Analysis Applied to Phase Contrast Magnetic Resonance Imaging of the Heart

Abstract: Abstract-Phase contrast magnetic resonance imaging is performed to produce flow fields of blood in the heart. The aim of this study is to demonstrate the state of change in swirling blood flow within cardiac chambers and to quantify it for clinical analysis. Velocity fields based on the projection of the three dimensional blood flow onto multiple planes are scanned. The flow patterns can be illustrated using streamlines and vector plots to show the blood dynamical behavior at every cardiac phase. Large-scale v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 69 publications
2
39
0
Order By: Relevance
“…[17][18][19][20] Hints of these structures come to us from studies performed with methods such as contrast, 21,22 Doppler, 5 and particle velocimetry. 23 These flow structures can be detected in planes through the heart (Figure 1; supplemental Video I), including the variable size and positions of vortical flow 24 that in normal hearts is initiated early in diastole underneath the mitral valve leaflets and reaccelerates during atrial contraction.…”
Section: Flow In the Normal Lv: The Surprise Insidementioning
confidence: 99%
“…[17][18][19][20] Hints of these structures come to us from studies performed with methods such as contrast, 21,22 Doppler, 5 and particle velocimetry. 23 These flow structures can be detected in planes through the heart (Figure 1; supplemental Video I), including the variable size and positions of vortical flow 24 that in normal hearts is initiated early in diastole underneath the mitral valve leaflets and reaccelerates during atrial contraction.…”
Section: Flow In the Normal Lv: The Surprise Insidementioning
confidence: 99%
“…Another computational approach has been described recently that uses a control volume technique to analyze the mechanism of energy losses in functional single ventricle patients after Fontan palliation. 15,34,36,38 Recently, CMR-based flow simulations have been performed by Wong et al 39 and Morbiducci et al 25 to access blood flow patterns in heart, and by Funamoto et al 16 for cerebral aneurism that do not require pressure measurements.…”
Section: Introductionmentioning
confidence: 98%
“…However, it was able to be shown that vortex flows can occur at non-physiological sites in various diseases. Aneurysms, pulmonary hypertension, and various heart diseases correlate with the occurrence and the intensity of vortex flows [18,19]. In addition, various valve pathologies and the use of artificial heart valves result in different vortex flows [20].…”
Section: Vortex Flowsmentioning
confidence: 99%